Phase Retardation Analysis in a Rotated Plane-Parallel Plate for Phase-Shifting Digital Holography - Igor Shevkunov; Nikolay V. Petrov (Journal of Imaging, 2022)
In this paper, we detail a phase-shift implementation in a rotated plane-parallel plate (PPP). Considering the phase-shifting digital holography application, we provide a more precise phase-shift estimation based on PPP thickness, rotation, and mutual inclination of reference and object wavefronts. We show that phase retardation uncertainty implemented by the rotated PPP in a simple configuration is less than the uncertainty of a traditionally used piezoelectric translator. Physical experiments on a phase test target verify the high quality of phase reconstruction.